ALIH KODE DAN CAMPUR KODE PADA NASKAH DRAMA KABAYAN MENCARI CINTA KARYA SALSABILA PIRIYANTI - Ria Suryani; Ian Sopian (IKIP Siliwangi, 2019)
This article was created to analyze the languages used for dialogue in the contents of the manuscript entitled